Successful implementation of a rural extracorporeal photopheresis program for the treatment of cutaneous T‐cell lymphoma and chronic graft‐versus‐host disease in a rural hospital. Issue 6 (17th February 2015) - Weber, Litchia L.; Dunbar, Nancy M.; Meehan, Kenneth R.; Szczepiorkowski, Zbigniew M.; Lansigan, Frederick
Abstract : Objective: Extracorporeal photopheresis (ECP) is currently standard therapy for cutaneous T‐cell lymphoma (CTCL) and Graft‐versus‐host disease (GVHD). Of the many challenges associated with outpatient ECP treatments, commuter travel to capable facilities can fragment and compromise the patient care. In 2008, our hospital implemented an ECP program providing patients to a treatment center over 120 minutes away. This study was undertaken to describe our experience with the establishment of a regional ECP program. Methods: A retrospective review using a standardized template was performed of patients treated from May 2008 to 2012. The response to treatment was analyzed after a minimum of eight procedures. A partial response to treatment in individuals with CTCL, was more than 50% skin improvement, and GVHD, a reduction in steroid dose by 50%, liver function test improvement or documented improvement in skin findings. Results: Of the 34 patients treated, 11 were for CTCL and 23 for GVHD. 95.8% of the 1, 071 planned procedures were successfully. The average procedure time was 186 min for the UVAR‐XTSTM and 93 min for the CELLEXTM. Patients travelled a median of 65.7 miles (range 4–133 miles). The median duration of therapy was 6 months (range 2–23) for CTCL and 5 months (range 1–27) for GVHD. A clinical benefit was observed in 7 of 11 (63.6%) patients with CTCL and in 15 of 23 (65.2%) with GVHD. Conclusion: Our regional ECP program was a viable option in improving access to care for patients requiring treatment for CTCL and chronic GVHD. J. Clin. Apheresis 30:359–363, 2015. © 2015 Wiley Periodicals, Inc.